Development and testing of an online course on the second victim phenomenon: a three-dimensional evaluation and proof of concept - Bexten, Tobias; Kubitz, Jens Christian; Kamphausen, Anne; Roesner, Hannah; Strametz, Reinhard (Frontiers in Public Health, 2025)
BackgroundThe Second Victim Phenomenon (SVP) refers to the emotional, psychological, and professional consequences healthcare professionals (HCPs) may face following adverse patient events. Despite its prevalence, awareness and structured education on SVP remain limited.ObjectiveThis study aimed to further develop and evaluate an online course to increase knowledge and awareness of SVP among HCPs via a multidimensional evaluation approach.MethodsA structured e-learning course was developed on the basis of an extensive literature review and qualitative content analysis. Seven learning objectives organized into four thematic categories were integrated. The course was evaluated through semistructured interviews, which were analyzed on the basis of Mayring’s qualitative method. After the course was adjusted accordingly, it was quantitatively evaluated, including pre- and postcourse knowledge tests and a course evaluation survey.ResultsThe interview feedback highlighted the relevance to clinical practice, strong structure, and interactivity, although participants recommended more practical examples and enhanced quiz feedback. After the adjustment, the knowledge score improved from a precourse average of 74.07 percent to a postcourse average of 87.96 percent [t(df) = 3.51, p = 0.005, d = 1.01]. The participants also reported an increase in their self-assessed knowledge. The course received high ratings for usability and satisfaction, with a mean overall score of 1.75 (where 1 is the best and 6 is the worst).ConclusionThis pilot study demonstrated that a structured online course can effectively improve knowledge and awareness of SVP among HCPs. Broader implementation, including integration into healthcare curricula, may support early recognition and mitigation of SVP-related consequences.